Gene Expression of Specific Enological Traits in Wine Fermentation - Martinez-Fernandez, C; Ganga-Munoz, M; Garcia-Mena, V (2013)
Background: Wine fermentation is a dynamic process and yeast has a precise genic regulation system that allow them to coordinate the gene transcription levels. However, the fermentation stage at which there is a great variation in the genic expression associated to a particular enological trait is often unknown and there are no simple experimental approaches to define it. Results: To identify the most adequate stage in which to evaluate the expression of the genes associated to specific enological traits we identified three stages of fermentation using the industrial strain EC1118. These stages, called early (0-16.4 hrs), middle (16.4-88.7 hrs) and late (88.7 hrs onwards), were characterized according to changes in the speed of CO2 production. The greatest nitrogen consumption velocity (1.016 g/L h) was achieved in the early stage. The most significant changes in the consumption of sugar and ethanol production acceleration occurred in the middle stage, and the greatest velocity of ethanol production (0.043%/h) and fructose consumption (0.338 g/L h) occurred in the late stage. The expression profiles for a set of genes characteristic of these processes were clearly defined during the stages of fermentation: identifying a peak for the genes related to the consumption of nitrogen during the early stage, followed by an increase in the expression of genes related to the consumption of sugars in the middle stage. Finally, during the late stage there is a decrease in the expression of genes involved in the consumption of sugar, except for HXT3 the levels of which remain high. Conclusions: The kinetic and transcriptional profiles of the enological traits under study are clearly distinct and each is associated to a particular stage of the fermentation. Our results confirm that CO2 production is a simple parameter to estimate the stages of the fermentation. Therefore, using the kinetics of CO2 loss it is possible to select the most adequate moment to study the expression of genes associated to the main enological traits: sugar consumption and production of nitrogen and ethanol.